Broad-spectrum fungal resistance in sorghum is conferred through the complex regulation of an immune receptor gene embedded in a natural antisense transcript. Issue 5 (9th January 2022) - Lee, Sanghun; Fu, Fuyou; Liao, Chao-Jan; Mewa, Demeke B; Adeyanju, Adedayo; Ejeta, Gebisa; Lisch, Damon; Mengiste, Tesfaye
Abstract: Sorghum ( Sorghum bicolor ), the fifth most widely grown cereal crop globally, provides food security for millions of people. Anthracnose caused by the fungus Colletotrichum sublineola is a major disease of sorghum worldwide. We discovered a major fungal resistance locus in sorghum composed of the nucleotide-binding leucine-rich repeat receptor gene ANTHRACNOSE RESISTANCE GENE1 ( ARG1 ) that is completely nested in an intron of a cis-natural antisense transcript (NAT) gene designated CARRIER OF ARG1 ( CARG ). Susceptible genotypes express CARG and two alternatively spliced ARG1 transcripts encoding truncated proteins lacking the leucine-rich repeat domains. In resistant genotypes, elevated expression of an intact allele of ARG1, attributed to the loss of CARG transcription and the presence of miniature inverted-repeat transposable element sequences, resulted in broad-spectrum resistance to fungal pathogens with distinct virulence strategies. Increased ARG1 expression in resistant genotypes is also associated with higher histone H3K4 and H3K36 methylation. In susceptible genotypes, lower ARG1 expression is associated with reduced H3K4 and H3K36 methylation and increased expression of NATs of CARG . The repressive chromatin state associated with H3K9me2 is low in CARG -expressing genotypes within the CARG exon and higher in genotypes with low CARG expression. Thus, ARG1 is regulated by multiple mechanisms and confers broad-spectrum, strong resistance to fungal pathogens. Abstract : Broad-spectrum fungal resistance in sorghum is conferred by an immune receptor locus regulated by miniature inverted-repeat transposable elements, antisense transcripts, and histone methylation.